A Randomized, Double-Blind, Placebo-Controlled Trial of Low-Dose Sertraline in Young Children With Fragile X Syndrome. Issue 8 (October 2016) - Greiss Hess, Laura; Fitzpatrick, Sarah E.; Nguyen, Danh V.; Chen, Yanjun; Gaul, Kimberly N.; Schneider, Andrea; Lemons Chitwood, Kerrie; Eldeeb, Marwa Abd Al Azaim; Polussa, Jonathan; Hessl, David; Rivera, Susan; Hagerman, Randi J.
ABSTRACT: Objective: Observational studies and anecdotal reports suggest that sertraline, a selective serotonin reuptake inhibitor, may improve language development in young children with fragile X syndrome (FXS). Methods: The authors evaluated the efficacy of 6 months of treatment with low-dose sertraline in a randomized, double-blind, placebo-controlled trial in 52 children with FXS aged 2 to 6 years. Results: Eighty-one subjects were screened for eligibility, and 57 were randomized to sertraline (27) or placebo (30). Two subjects from the sertraline arm and 3 from the placebo arm discontinued. Intent-to-treat analysis showed no difference from placebo on the primary outcomes: the Mullen Scales of Early Learning (MSEL) expressive language (EL) age equivalent and Clinical Global Impression Scale—Improvement. However, analyses of secondary measures showed significant improvements, particularly in motor and visual perceptual abilities and social participation. Sertraline was well tolerated, with no difference in side effects between sertraline and placebo groups. No serious adverse events occurred. Conclusion: This randomized controlled trial of 6 months of sertraline treatment showed no primary benefit with respect to early EL development and global clinical improvement. However, in secondary exploratory analyses, there were significant improvements seen on motor and visual perceptual subtests, the cognitive T score sum on the MSEL, and on one measure of social participation on the Sensory Processing Measure—Preschool. Furthermore, post hoc analysis found significant improvement in early EL development as measured by the MSEL among children with autism spectrum disorder on sertraline. Treatment appears safe for this 6-month period in young children with FXS, but the authors do not know the long-term side effects of this treatment. These results warrant further studies of sertraline in young children with FXS using refined outcome measures as well as longer term follow-up studies to address long-term side effects of low-dose sertraline in early childhood.